Decision Model of the Best Investment Opportunity in Coal Mine Project Based On Real Option - Zhu Yongfei; Li Congdong (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The traditional decision-making methods of investment decision about coal mine projects have many deficiencies. Decision model of coal mine project option is proposed in paper . Firstly, analysis the characteristics which include uncertainty and irreversibility of physical option and build a suitable model after researching the significance ,then decide the best time though the coal mine project. Finally, case analysis presents the application of this method and provides strong theoretical basis for decision in coal mine project. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2857